Quantification of nonlinear distortion in optical links based on the 400ZR standard - Gosmin, João Pedro Innocente [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Coherent optical systems have transformed modern networks by enabling high transmission rates with elevated spectral efficiency, becoming increasingly common in short- and medium-reach links such as those defined by the 400 Gb/s coherent optical interface standard (400ZR) standard. These systems rely on coherent reception and intensive Digital Signal Processing (DSP) processing to compensate for linear effects, but they remain limited by noise accumulation—primarily amplified spontaneous emission (ASE) noise from optical amplifiers—as well as by fiber nonlinearities such as self-phase modulation (SPM), cross-phase modulation (XPM), and four-wave mixing (FWM), which distort the constellation and reduce the optical signal-to-noise ratio (OSNR) margin. This work investigates, through a simulator fully developed in Python, the combined impact of these impairments on the performance of 400ZR-compliant systems, evaluating the evolution of the constellations, symbol-to-symbol interactions, distortion propagation, and the resulting penalties in bit-error-rate performance. The results show that, even in short-reach scenarios, nonlinear effects significantly influence the high-power regime, limiting the achievable reach and highlighting the need for effective compensation strategies. The analyses provided contribute to a deeper understanding of the operational limits of 400ZR links and offer essential insights for improving mitigation techniques applicable to future higher-capacity coherent interfaces.

Os sistemas transformaram as redes modernas ao permitir altas taxas de transmissão com elevada eficiência espectral, tornando-se cada vez mais comuns em enlaces de curta e média distância, como aqueles definidos pelo padrão 400ZR. Esses sistemas utilizam recepção coerente e intenso DSP para compensar efeitos lineares, mas continuam limitados pela acumulação de ruído — principalmente ASE proveniente de amplificadores ópticos — e pelas não linearidades da fibra, como SPM, XPM e FWM, que distorcem a constelação e reduzem a margem de OSNR. Este trabalho investiga, por meio de um simulador desenvolvido integralmente em Python, o impacto conjunto desses efeitos no desempenho de sistemas padronizados em 400ZR, avaliando a evolução das constelações, a interação entre símbolos, a propagação das distorções e as penalidades observadas na taxa de erro de bit. Os resultados mostram que, mesmo em enlaces curtos, as não linearidades influenciam significativamente o regime de alta potência, restringindo o alcance e evidenciando a necessidade de estratégias eficazes de compensação. As análises obtidas contribuem para o entendimento dos limites operacionais do 400ZR e oferecem informações essenciais para o aprimoramento de técnicas de mitigação aplicáveis às futuras interfaces coerentes de maior capacidade.
Quantificação da distorção não linear em enlaces ópticos com padrão 400 ZR
Keywords: Comunicações ópticas; Engenharia; Ótica não linear; Telecomunicações